Application of doses of soil conditioning associated with mineral and organic fertilization in lettuce cultivation (Research, Society and Development, 2020)
Lettuce is the herbaceous vegetable most cultivated and commercialized in Brazil, with high economic importance. The objective of this work was to evaluate the effect of soil conditioner based on wood residue and bovine ruminal residue, associated with chemical and organic fertilization in lettuce. The experiment was conducted in the field in the olive growing sector of the Institute Federal of Mato Grosso- Campus Juína, from April to August 2018.The experimental design was a randomized complete block design (3x5), composed by the combination of three fertilizations (organic, mineral and control) and five soil conditioning doses (0, 10, 20, 30 and 40 Mg ha ha-1), with four replications. At the end of the experiment the relative content of total chlorophyll; diameter of the head; collection diameter; total and commercial leaf number count and total fresh; phytomass commercial fresh phytomass; non-commercial dry phytomass; commercial dry phytomass. The chemical fertilization showed to be more efficient for the growth of lettuce plants, while the application of the soil conditioner promoted linear additions in the lettuce production. The study shows that through the application of the soil conditioner associated with mineral and organic fertilization, it is possible to promote productive gains in the lettuce crop. The chemical fertilization showed to be more efficient for the growth of lettuce plants, while the application of the soil conditioner promoted linear additions in the lettuce production. The association between the soil conditi oner at the highest dose and chemical fertilization was shown to be efficient for increasing lettuce productivity.